Cold Pool Dynamics Shape the Response of Extreme Rainfall Events to Climate Change - Lochbihler, Kai; Lenderink, Geert; Siebesma, A. Pier (Journal of advances in modeling earth systems, 2021)
There is increasing evidence that local rainfall extremes can increase with warming at a higher rate than expected from the Clausius‐Clapeyron (CC) relation. The exact mechanisms behind this super‐CC scaling phenomenon are still unsolved. Recent studies highlight invigorated local dynamics as a contributor to enhanced precipitation rates with warming. Here, cold pools play an important role in the process of organization and deepening of convective clouds. Another known effect of cold pools is the amplification of low‐level moisture variability. Yet, how these processes respond to climatic warming and how they relate to enhanced precipitation rates remains largely unanswered. Unlike other studies which use rather simple approaches mimicking climate change, we present a much more comprehensive set of experiments using a high‐resolution large eddy simulation (LES) model. We use an idealized but realistically forced case setup, representative for conditions with extreme summer precipitation in midlatitudes. Based on that, we examine how a warmer atmosphere under the assumption of constant and varying relative humidity, lapse rate changes and enhanced large‐scale dynamics influence precipitation rates, cold pool dynamics, and the low‐level moisture field. Warmer conditions generally lead to larger and more intense events, accompanied by enhanced cold pool dynamics and a concurring moisture accumulation in confined regions. The latter are known as preferred locations for new convective events. Our results show that cold pool dynamics play an increasingly important role in shaping the response of local precipitation extremes to global warming, providing a potential mechanism for super‐CC behavior as subject for future research. Plain Language Summary Observations and models show that rain extremes are increasing with global warming. Aggregated over large areas and long‐time intervals, this increase will roughly follow the higher water holding capacity of air at a warmer temperature. However, local extreme storms show a much stronger response. This indicates that, in addition to a potentially greater local moisture availability in a warmer climate, rain events consume moisture from a larger area. Investigating this aspect requires expensive high‐resolution models. We do this by simulating a typical summer day with heavy rainfall on an area roughly the size of the Netherlands. By changing the temperature along with other characteristics of the atmosphere, we mimic the impact of climatic change. Our results show that warmer conditions generally lead to larger and more intense storms. Furthermore, we find that moisture transport near the surface through the winds created by storms plays an important role. This can result in an accumulation of moisture at certain locations that stems from greater distances away. Freshly developing storms eventually can harvest this additional moisture. This feedback process intensifies under warmer and moister conditions and provides a potential mechanism for the strong increase of local rainfall extremes in a warmer climate. Key Points Warmer conditions lead to more intense and larger rain cells Rain cell properties show distinct, well‐defined relations with cold pool properties Largest variations at high temperature, with reductions of RH leading to very strong cold pool dynamics and vigorous rain systems